Hubungan Kecerdasan Spiritual Perawat dengan Perilaku Caring Perawat di Rawat Inap RSUD Rasidin Padang Tahun 2025 - Mona Anggia Fiska (CV. ITTC INDONESIA, 2026)
Poor caring behavior in nurses can be detrimental to patients, and one factor influencing it is nurses' spiritual intelligence. Caring behavior among nurses at Rasidin Hospital is still lacking, and nurses' spiritual intelligence remains low. This study aimed to determine the relationship between nurses' spiritual intelligence and the caring behavior of inpatient nurses at Rasidin Hospital, Padang in 2025. This was a quantitative, correlative analytical study using a cross-sectional approach. The population consisted of 63 respondents, with a sample of 53 respondents selected through total sampling. Data were collected from July 21–29, 2025, using the Caring Behavior Inventory (CBI) and the SISRI-24. Data were analyzed using univariate and bivariate chi-square tests with a p-value < 0.05. The results showed that less than half (47.4%) of respondents had low spiritual intelligence, and more than half (54.4%) had poor caring behavior. There was a significant correlation between nurses' spiritual intelligence and caring behavior, with a p-value of 0.001 (p<0.05). In conclusion, there is a relationship between nurses' spiritual intelligence and caring behavior. The Director and nursing department are expected to improve nurses' spiritual intelligence to enhance caring behavior and the quality of nursing care.